A review of microbiomes in carp polyculture systems - Ngan, Bui Ngoc Minh; Heyse, Jasmine; Delamare-Deboutteville, Jerome; Props, Ruben; Shelley, Colin (WorldFish, 2023)
This review describes the current state of research on carp microbial communities. This includes research on bacteria, microalgae and viruses in carp polyculture, as well as the current technology used to detect, monitor and describe microbiomes. In addition, the effects of inputs such as probiotics, antibiotics, fertilizer, feed and sanitizers on microbial communities, water quality and so on are also discussed. Studying microbial composition, and the factors that impact them, can help better understand the microbiome of both carp and carp polyculture systems.